China : the novel - Rutherfurd, Edward (Doubleday, 2021)
"Edward Rutherfurd has enthralled millions of people with his grand, sweeping historical sagas that tell the history of an iconic place over multiple generations. Now, in China: The Novel, Rutherfurd takes readers into the rich and fascinating milieu of the Middle Kingdom. The story begins in 1839, at the dawn of the first Opium War. An English merchant arrives in the restricted port of Canton (Guangzhou), seeking to make his fortune trading opium. But the tide of addiction is decimating the Chinese population--a young scholar accompanies his Mandarin master on a mission from the emperor to shut down the trade. Thus begins an epic tale chronicling China's struggle to regain their ancient land and culture from the domination of the Western powers, which culminates in the revolution of 1911, and the ultimate rise of the Communist regime. We meet a young village wife struggling with the rigid traditions of her people, Manchu empresses and warriors, the powerful eunuchs of the Forbidden City, rapacious English opium dealers and savvy Chinese pirates, artists, concubines, scoundrel's and heroes. Rutherfurd chronicles the rising and falling fortunes of members of Chinese, British, and American families, as they negotiate the tides of history. Along the way, in his signature style, Rutherfurd provides a deeply researched portrait of Chinese history and society, its ancient traditions and great upheavals, and China's emergence as a rising global power. We are treated to romance and adventure, battles and intrigues, grinding struggle and incredible fortune. China: The Novel brings to life the rich terrain of this vast and constantly evolving country. From Shanghai to Beijing to the Great Wall, Rutherfurd chronicles the turbulent rise and fall of empires as the colonial West meets the opulent and complex East in a dramatic struggle between cultures and people. Extraordinarily researched and majestically told, Rutherfurd paints a thrilling portrait of one of the most singular and remarkable countries in the world"--